2014
DOI: 10.4172/2327-5073.1000160
|View full text |Cite
|
Sign up to set email alerts
|

Candida-Associated Denture Stomatitis: Clinical Relevant Aspects

Abstract: Candida-associated denture stomatitis is a common fungal infection that affects removable denture wearers. Although Candida spp are considered commensal fungal in the oral cavity, changes in local and/or systemic predisposing factors related to the host conditions may lead to pathogenic form and cause disease. The clinical manifestations are usually associated with the predisposing factors, changing from no symptoms to severe pain and difficulty swallowing. The therapeutic strategies commonly adopted in the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(29 reference statements)
0
6
0
2
Order By: Relevance
“…Patients with ill-fitting or inadequately cleaned dentures have been reported to have a higher risk of denture stomatitis due to denture plaques [ 41 ]. Complications such as inflammation and redness of the buccal mucosa or ulcer formation lead to dysfunction due to dentures, resulting in decreased bite force and salivary flow rate [ 42 ]. This study demonstrated that prosthetic treatment improved the salivary flow rate and reduced the C. albicans count, thus improving intraoral symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ill-fitting or inadequately cleaned dentures have been reported to have a higher risk of denture stomatitis due to denture plaques [ 41 ]. Complications such as inflammation and redness of the buccal mucosa or ulcer formation lead to dysfunction due to dentures, resulting in decreased bite force and salivary flow rate [ 42 ]. This study demonstrated that prosthetic treatment improved the salivary flow rate and reduced the C. albicans count, thus improving intraoral symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Ketokonazol je hepatotoksičan i može izazvati srčane aritmije ukoliko se primenjuje u kombinaciji sa makrolidnim antibioticima ili sa antihistaminicima. Amfotericin B se ranije intravenozno primenjivao u tretmanu kandidom izazvanog proteznog stomatitisa, ali je danas njegova primena redukovana zbog nefrotoksičnosti 48 . Amfotericin B za lokalnu primenu u obliku 3% losiona primenjuje se dva puta dnevno, ali ima neprijatan ukus, pa može izazvati gastrointestinalne smetnje poput mučnine, povraćanja i dijareje 34 .…”
Section: The Therapy Of Denture Stomatitisunclassified
“…Amphotericin B was previously intravenously used in the treatment of Candida-induced denture stomatitis. However, its administration has been reduced because of its nephrotoxic effect 48 . Amphotericin B for topical application in the form of a 3% lotion is applied twice a day, but it has an unpleasant taste and may cause gastrointestinal disturbances such as nausea, vomiting and diarrhea 34 .…”
Section: The Therapy Of Denture Stomatitismentioning
confidence: 99%
“…18 La mayoría de los pacientes portadores de prótesis consideran que las irritaciones palatinas que presentan son consecuencias normales del uso de la prótesis, desconocen que ésta puede ser causada por la presencia de microorganismos y no le prestan la debida importancia. 19,20 El objetivo de esta investigación fue estudiar prevalencia de estomatitis subprotésica asociada a Candida albicans en pacientes portadores de prótesis total superior removible, en centros de atención geriátrica (asilos) del Valle de Los Chillos, Ecuador.…”
Section: Introductionunclassified